A Righteousness Greater than that of the Scribes and Pharisees (Mt 5:20): Righteousness for the Kingdom of God (Hekima Review, 2007)
An examination of the seven passages shows that two references are found in narratives which have parallels in Luke’s gospel. These can therefore be considered as a Matthaean rework of Q material. In these two instances, the reworking consists precisely in bringing into the Q material the concept of righteousness. That is the case of Mt 5:6 (“Blessed are those who hunger and thirst for righteousness, for they will be filled”), whereas Lk 6:21 simply reads: “Blessed are you who are hungry now, for you will be filled,” and of Mt 6:33(“Strive first for the kingdom of God and its righteousness”), Lk 12:31 has simply: “Seek his kingdom and these things shall be yours as well.” The other references (3:15, 5:10, 5:20, 6:1, 21:32) are peculiar to Matthew’s redactional economy and can be considered as M material.